Supramolecular Self-Assembly and Phase Transformations in Aqueous Systems Based on Chitosan and Sulfonated Metallophthalocyanines - Lipatova, I. M.; Mezina, E. A.; Yusova, A. A. (Russian journal of general chemistry, 2019)
The supramolecular self-assembly in mixed low-concentrated aqueous solutions of chitosan and sulfonated metallophthalocyanines was examined by spectroscopic and dynamic light scattering techniques. The research subjects were Cu(II) and Co(II) tetrasulfophthalocyaninates, as well as Cu(II) phthalocyaninate containing sulfonate groups and a vinylsulfonic substituent. The resulting supramolecular complexes were characterized by a reproducible stoichiometric composition, as well as by the ability to move slowly into a colloidal-dispersed state. Phase separation was preceded by a metastable state with unchanging spectral characteristics, for which the size and ζ-potential of the primary supramolecular particles were determined.